PENGARUH CITRA MEREK, PERSEPSI HARGA, DAN SOCIAL MEDIA MARKETNG TERHADAP KEPUTUSAN PEMBELIAN PRODUK MORI-MORI - Ni Made Mira Yurika; I Gusti Ayu Imbayani; I Made Surya Prayoga (EMAS, 2023)
Purchasing decision is a concept in which purchasing decision making will be a consideration for consumers to make buying and selling transactions of goods or services. Purchasing decisions are an important thing to note because this will certainly be a consideration of how a marketing strategy will be carried out by the company. Purchase decisions made by consumers are inseparable from the factors that influence consumers to make purchases. One of the factors that can influence consumers in making decisions about a product is brand image, price perception, and social media marketing. The purpose of this study was to determine the effect of brand image, price perception, and social media marketing on purchasing decisions for mori mori products. This research is quantitative by giving a score to each respondent's answer. The population of this research is people who live in the city of Gianyar. The sampling technique used in this study is nonprobability sampling. The distribution of questionnaires was carried out using accidental sampling techniques with 75 respondents. The data analysis technique used is multiple linear analysis. The results of this study indicate that brand image has a positive and significant effect on purchasing decisions for Mori-Mori products, Tampaksiring. Price perception has a positive and significant effect on purchasing decisions for Mori-Mori products, Tampaksiring. Social media marketing has a positive and significant effect on purchasing decisions for Mori-Mori products, Tampaksiring